Improving the Pharmacodynamics and In Vivo Activity of ENPP1‐Fc Through Protein and Glycosylation Engineering. Issue 1 (20th October 2020) - Stabach, Paul R.; Zimmerman, Kristin; Adame, Aaron; Kavanagh, Dillon; Saeui, Christopher T.; Agatemor, Christian; Gray, Shawn; Cao, Wenxiang; De La Cruz, Enrique M.; Yarema, Kevin J.; Braddock, Demetrios T.
Abstract : Enzyme replacement with ectonucleotide pyrophosphatase phospodiesterase‐1 (ENPP1) eliminates mortality in a murine model of the lethal calcification disorder generalized arterial calcification of infancy. We used protein engineering, glycan optimization, and a novel biomanufacturing platform to enhance potency by using a three‐prong strategy. First, we added new N‐glycans to ENPP1; second, we optimized pH‐dependent cellular recycling by protein engineering of the Fc neonatal receptor; finally, we used a two‐step process to improve sialylation by first producing ENPP1‐Fc in cells stably transfected with human α‐2, 6‐sialyltransferase (ST6) and further enhanced terminal sialylation by supplementing production with 1, 3, 4‐ O ‐Bu3 ManNAc. These steps sequentially increased the half‐life of the parent compound in rodents from 37 hours to 67 hours with an added N‐glycan, to 96 hours with optimized pH‐dependent Fc recycling, to 204 hours when the therapeutic was produced in ST6‐overexpressing cells with 1, 3, 4‐ O ‐Bu3 ManNAc supplementation. The alterations were demonstrated to increase drug potency by maintaining efficacious levels of plasma phosphoanhydride pyrophosphate in ENPP1‐deficient mice when the optimized biologic was administered at a 10‐fold lower mass dose less frequently than the parent compound—once every 10 days vs. 3 times a week. We believe these improvements represent a general strategy to rationally optimize protein therapeutics.